DOP37 Efficacy and safety of 3 years of continuous ozanimod treatment: an interim analysis of the True North open-label extension study. (30th January 2023) - Danese, S; Abreu, M T; Wolf, D C; Canavan, J B; Jain, A; Wu, H; Petersen, A; Charles, L; Panaccione, R; Afzali, A
Abstract: Background: The phase 3 True North (TN) study demonstrated the efficacy and safety of ozanimod over 52 weeks in patients with moderately to severely active ulcerative colitis (UC). Patients completing 52 weeks of TN were eligible for the ongoing TN open-label extension (OLE) assessing the long-term efficacy and safety of ozanimod. Presented is the interim analysis of the TN OLE in patients with approximately 3 years of continuous ozanimod treatment. Methods: This analysis evaluated patients who achieved clinical response after receiving 52 weeks of continuous ozanimod 0.92 mg during TN and subsequently entered the TN OLE (data cutoff: 10 January 2022, the point at which the OLE Week 94 disposition was available for patients). Patient-reported (rectal bleeding and stool frequency) and clinician-reported (Physician's Global Assessment) outcomes were collected. Centrally read endoscopy was performed at OLE Weeks 46 and 94 (98 and 146 weeks of continuous ozanimod treatment, respectively). Efficacy data (clinical remission, clinical response, endoscopic improvement, and corticosteroid-free remission) were evaluated in the intent-to-treat population at OLE Weeks 46 and 94 using observed case (OC) and nonresponder imputation (NRI) analyses. Partial Mayo scores (PMS) were assessed from TN baseline to OLE Week 94. Adverse events were monitored throughout TN and the subsequent OLE. Results: In all, 131 patients entered the OLE after achieving clinical response following 52 weeks of continuous ozanimod during TN; at data cutoff, 87.0% completed OLE Week 46 (98 weeks of continuous ozanimod) and 71.8% completed OLE Week 94 (146 weeks of continuous ozanimod). Patients had a mean age of 44 years and 52% were female. Most (68%) had left-sided UC disease, 24% had concomitant corticosteroid use at TN baseline, and 32% had prior exposure to tumour necrosis factor inhibitors. Most patients achieved clinical remission, clinical response, corticosteroid-free remission, and endoscopic improvement at OLE Week 46 in the OC (Figure 1A) and NRI (Figure 1B) analyses. At OLE Week 94, 91.4% of patients achieved clinical response in the OC analysis (NRI, 56.5%). Ozanimod was associated with a reduction in mean PMS during TN (PMS=6.2 at Week 0 and 0.9 at Week 52), and this was sustained through OLE Week 94 (PMS=0.9) (Figure 2). No new safety findings emerged from this analysis. Conclusion: This interim analysis of the TN OLE found that most of the patients who achieved clinical response after 1 year of ozanimod had sustained efficacy for an additional 2 years. No new safety signals were observed with long-term ozanimod use.